EXTRACTION OF IRON FROM RED MUD USING PALM KERNEL SHELL CHARCOAL AND COAL REDUCTANT AT TEMPERATURES 1350 Â°C â 1450 Â°C - Dharma Hendrawan, Rizqi
The Bayer process is used to convert bauxite ore into alumina, which produces waste in the form of bauxite residue. If the residue is not managed properly, it can harm the surrounding environment. Bauxite residue, which has a high iron content (> 30%), has a potential to be used as raw material for iron-steel making by reducing the iron oxide contained therein. Indonesia has the most significant palm oil production globally, which produces a by-product in the form of palm kernel shell that can be processed as palm kernel shell charcoal (PKSC). Therefore, it is necessary to treat the waste of bauxite residue and oil palm shells to reduce environmental problem and increase the use value of the two components. This research utilizes palm shell charcoal as a reducing agent in reducing iron oxide from bauxite residue to produce iron metal.